Scale-dependent foraging costs: habitat use by rock hyraxes (Procavia capensis) determined using giving-up densities - Druce, Dave J.; Brown, Joel S.; Castley, J. Guy; Kerley, Graham I. H.; Kotler, Burt P.; Slotow, Rob; Knight, Mike H. (Oikos, 2006)
Individuals select for habitats at different scales. Can a species' response to different spatial and temporal heterogeneities be placed in a common currency? Is it possible to rank the relative importance of different habitat features on the organism's behavior and ecology? Do the effects of different spatial and temporal heterogeneities interact in predictable ways? To address these questions, we quantified hyrax habitat use at a series of rocky outcrops (koppies) and an isolated gorge in Augrabies Falls National Park, South Africa. We measured the hyraxes' perceptions of feeding opportunities and costs using giving-up densities (GUDs) within experimental food patches. At very small spatial scales (2-3 m), we tested whether hyraxes have lower GUDs under cover (shrubs or rocks) or 2-3 m away in the open. Hyraxes valued cover highly, consistently showing lower GUDs in cover microhabitats. This preference did not result from differences in energetic costs, as hyraxes did not track sun in winter or shade in summer. At moderate spatial scales (10- 80 m), we tested whether hyraxes act as central place foragers with lower GUDs closer to their dens. GUDs increased with increasing distance to dens at four koppies, but not at the gorge. At larger spatial scales, preferences differed between colonies based on differences in habitat structure, with hyraxes on similar structures (koppies) behaving similarly. We evaluated how foraging costs varied with temporal heterogeneity within the day, among days, and among seasons. Hyraxes showed their lowest GUDs in the early mornings and late afternoons. Hyraxes shifted foraging locations among days, which may result from sentinels shifting location on consecutive days and/or hyraxes managing their food. Differences between GUDs during the various sample periods were not seasonally correlated. We conclude that spatial and temporal habitat utilization by hyraxes may be driven more by predation risk rather than other costs.